Bioequivalence study of two formulations of candesartan cilexetil tablet in healthy subjects under fasting conditions - Tjandrawinata RR; Setiawati E; Yunaidi DA; Simanjuntak R; Santoso ID; Susanto LW (Dove Medical Press, 2013)
Raymond R Tjandrawinata,1 Effi Setiawati,2 Danang Agung Yunaidi,2 Ronal Simanjuntak,2 Iwan Dwi Santoso,2 Liana W Susanto1 1Dexa Laboratories of Biomolecular Sciences (DLBS), Cikarang, Indonesia; 2Bioavailability and Bioequivalence Laboratory, PT Equilab International, Jakarta, Indonesia Introduction: The present study was conducted to compare the bioavailability of two candesartan cilexetil 16 mg tablet formulations (test and reference formulations). Materials and methods: This study was a randomized, single- blind, two-period, cross-over study which included 24 healthy adult male and female subjects under fasting conditions. The pharmacokinetic parameters were determined based on the concentrations of candesartan (CAS 139481-59-7), using ultra-pressure high-performance liquid chromatography with a tandem mass spectrometer detector. In each of the two study periods (separated by a washout period of 1 week), a single dose of test or reference product was administered. The pharmacokinetic parameters assessed were area under the plasma concentration time curve (AUC) from time 0 hours to 24 hours, AUC from time zero to infinity, the peak plasma concentration of the drug (Cmax), time to achieve the Cmax, and the elimination half-life. Results: The geometric mean ratios (90% confidence interval) of the test drug/reference drug for candesartan were 100.92% (92.15%–110.52%) for the AUC from 0 hours to 24 hours, 100.24% (92.24%–108.95%) for the AUC from time zero to infinity, and 106.71% (93.20%–122.18%) for the Cmax. The differences between the test and reference product in the time to achieve Cmax values and elimination half-life values were not statistically significant (P > 0.05). The 90% confidence intervals of the test/reference AUC ratio and Cmax ratio of candesartan were within the acceptance range for bioequivalence. There was no adverse event encountered during this bioequivalence study. Conclusion: It was concluded that the two candesartan tablet formulations (the test and reference product) were bioequivalent. Keywords: angiotensin-2 receptor antagonist, antihypertension, bioavailability, bioequivalence, candesartan, pharmacokinetics